1988
DOI: 10.1002/ana.410230416
|View full text |Cite
|
Sign up to set email alerts
|

Seizures following myelography with iopamidol

Abstract: Iopamidol, a water-soluble contrast medium, has been rarely associated with seizures. We describe 3 patients (from a series of 785) who had generalized tonic-clonic seizures after iopamidol myelography. Two of the patients underwent lumbar and one cervical myelography. There was a history of seizures in 2 patients, and the dose of iopamidol used in the patients who convulsed was high, ranging from 3,000 to 4,500 mg iodine. Despite the reported low incidence of complications with iopamidol, seizures may occur, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This can be exemplified by the rare epileptogenic effect of iopamidol in man (3,4,8). This very rare excitative/convulsive effect of iopamidol has been consistently revealed by the present animal model, both in this study and previously (7), only at the maximum dose/volume of 1.0 mllkg b.w., whereas the injection of 0.5 mllkg (2.6 times the maximum recommended clinical myelographic dose in the USA) failed to disclose this effect both previously (7) and in this study.…”
Section: Discussionsupporting
confidence: 84%
“…This can be exemplified by the rare epileptogenic effect of iopamidol in man (3,4,8). This very rare excitative/convulsive effect of iopamidol has been consistently revealed by the present animal model, both in this study and previously (7), only at the maximum dose/volume of 1.0 mllkg b.w., whereas the injection of 0.5 mllkg (2.6 times the maximum recommended clinical myelographic dose in the USA) failed to disclose this effect both previously (7) and in this study.…”
Section: Discussionsupporting
confidence: 84%
“…uchiyama et al 33 found elevated concentration of CSF iodine in their index case and not in 4 control cases, supporting evidence of a temporary breakdown of the blood-brain barrier. The cause of the blood brain barrier disruption is variably attributed to the hyperosmolality and chemotoxicity of contrast media 2,16,21,28,[43][44][45][46][47][48][49][50][51][52][53][54][55][56] . Studies suggest that contrast media penetrates the blood-brain barrier as a function of dosage, contact time, concentration of anions in the material, and lipophilic…”
Section: Resultsmentioning
confidence: 99%
“…The manufacturer recommends that 10 mL of the 300 mg/mL strength or 15 mL of the 200 mg/mL strength be utilized for this procedure (12). A case report utilizing the dose administered to our patient also reported an outcome of generalized tonicclonic seizure in a patient with no history of seizure disorder (13).…”
Section: Discussionmentioning
confidence: 62%